Community alcohol sales and opioid poisoning deaths: Alcohol serving space as a harm reduction opportunity - Cory M. Morton; Kristen Gilmore Powell; Michael Routhier; N. Andrew Peterson (BMC, 2024)
Abstract The concurrent use of opioids and alcohol is particularly dangerous for individuals. Alcohol is commonly seen in opioid overdose death toxicology reports and, concurrent use of alcohol and opioids is often reported by individuals across a diverse range of opioid use profiles. This study investigates whether there is a community-level relationship between alcohol sales and opioid-related overdose deaths to inform the situating of harm reduction efforts in spaces most likely to reduce substance-related harms. Using an ecological design, zip code-level data for New Hampshire were combined from the US Census Bureau's American Community Survey (sociodemographics), the National Alcohol Beverage Control Association (alcohol retail sales), and the NH Office of the Chief Medical Examiner (zip code level opioid poisoning deaths) to investigate the relationship between alcohol sales and opioid-related poisoning deaths at a community level in a state with the third highest rate of opioid poisoning deaths for the year the current study represents. Using a spatial error regression model approach, opioid-related poisoning deaths were higher in zip codes with greater population density and on-premise alcohol sales and were lower in zip codes with greater off-premise alcohol sales and area disadvantage. The findings here co-locate higher levels of on-premise alcohol sales and opioid-related poisoning deaths at a community-level, mirroring individual-level findings on the danger of mixing these two substances. Results inform harm reduction approaches by identifying substance use spaces where overdose prevention messaging or policy change may be most effective.